Surface Water Yield Model Part-I : Development and Validation - Reddy, K.S.; Bhattacharya, A.K.; Mishra, K.; Basu, G.C. (Journal of Soil and Water Conservation, 2022)
A surface water yield model was developed by integrating hydrologic soil cover complex method with the reservoir water budgetting. The model was validated over five microzvatersheds of varying sizes and different land covers in the Upper damodar Valley of the Chotanagpur region of Bihar. The major objective of the study was to obtain a realistic estimate of runoff from rainfall by establishing the most appropriate curve numbers for different land uses of denuded forest, agricultural land and bare land by a trial and error process. The final selection of curve numbers were made when the model predicted runoff agreed with the corresponding observed values within a pre-assigned tolerance limit.